Moral Foundations Predict Perceptions of Moral Permissibility of COVID-19 Public Health Guideline Violations in United States University Students - Bruchmann, Kathryn; LaPierre, Liya (Frontiers in Psychology, 2022)
In the U.S., the COVID-19 pandemic as become highly politicized and highly moralized. The current study explored whether participants’ (N=118) endorsements of binding versus individualizing moral foundations explained partisan differences in views and behaviors regarding COVID-19. Participants completed the moral foundations questionnaire before they indicated how morally permissible they thought it was to violate COVID-19 mandates, report others’ violations, or not get vaccinated. Additionally, they indicated their own prevention behaviors. Results show that endorsement of both individualizing and binding foundations explain partisan differences in moral permissibility ratings. Political conservatism predicted greater endorsement of binding foundations which in turn predicted seeing COVID-19 violations and not getting vaccinated as more morally permissible, and predicted fewer self-reported prevention behaviors. Endorsement of individualizing foundations predicted seeing violations as less morally permissible and reporting others’ violations as more morally permissible.